Policy Intentions on Inclusive Education for Students with Disabilities in Ethiopia: A Qualitative Study - Tesaka Mebratu; Alemayehu Teklemariam; Tilahun Achaw (Indonesian Journal of Education and Social Studies, 2024)
Despite international commitments to inclusive education (IE), many students with disabilities (SWDs) in Ethiopia face barriers to accessing education that meets their special needs. This study aimed to assess the inclusivity of existing policy frameworks for SWDs in the country. Using a multiple case study design, the data were collected through an analysis of relevant policy documents and semi-structured interviews with 16 educational practitioners selected through purposive sampling. The data were analyzed using an inductive content analysis approach. The findings revealed a lack of a distinct national IE policy in Ethiopia. Despite this, existing legal frameworks, programs, strategies, standards, plans, and implementation guidelines related to education provision do support the inclusion of SWDs. However, their practicality is limited due to the lack of education law, weak structural support, limited capacities and resources, restricted access to quality education for SWDs, unreliable data and reporting systems, and inadequate financing mechanisms for IE. To ensure IE for SWDs, Ethiopia must develop a national IE policy, strengthen its organizational structures, address resource constraints, and establish a reliable data system. These findings are crucial for policymakers and practitioners seeking to address the special educational needs of SWDs in Ethiopia.